2015
DOI: 10.1002/hyp.10424
|View full text |Cite
|
Sign up to set email alerts
|

Snowmelt and the hydrological interaction of forest-grassland ecosystems in Central Yakutia, eastern Siberia

Abstract: Abstract:In the last two decades the major focus of study in forest water and carbon balances in eastern Siberia has been on the effect of rain during the growing season. Little attention has been paid to the contribution of snowmelt water. The results of the present study indicate that weather conditions during the snowmelt period as well as the soil moisture conditions carried from the previous year's growing season strongly determined the water availability for the forest ecosystem at the beginning of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Toure et al (2016) evaluated offline CLM4-simulated snow using in situ observed snow depth and satellite snow cover data and found that the model underestimated the snow depth and showed early snowmelt. We compared the SWE monthly climatology from four simulations for 1980-2009 over eastern Siberia and the western United States (figure not shown) and found that SWE peaked in April and February, respectively, which were much earlier than in the observations (e.g., Lopez Caceres et al 2015). This explains the model runoff peak in May (vs observed peak in June) over eastern Siberia and the model runoff peak in March (vs observed peak in May) over the western United States in Fig.…”
Section: Runoffmentioning
confidence: 96%
“…Toure et al (2016) evaluated offline CLM4-simulated snow using in situ observed snow depth and satellite snow cover data and found that the model underestimated the snow depth and showed early snowmelt. We compared the SWE monthly climatology from four simulations for 1980-2009 over eastern Siberia and the western United States (figure not shown) and found that SWE peaked in April and February, respectively, which were much earlier than in the observations (e.g., Lopez Caceres et al 2015). This explains the model runoff peak in May (vs observed peak in June) over eastern Siberia and the model runoff peak in March (vs observed peak in May) over the western United States in Fig.…”
Section: Runoffmentioning
confidence: 96%
“…However, some polarimetric parameters, including the dominant eigenvalue and co-polarization coherences exhibit characteristic differences between two ground sites only in frozen conditions. According to the literature [23][24][25][26][27], soils and active layers in forested areas are distinctive from those in open areas by the thermal condition, active layer thickness, infiltration and evaporation rates, salinity and thickness of the shielding layer. Consequently, although the causal mechanisms about these characteristic scattering properties cannot be confirmed at this stage, polarimetric scattering analysis also reveals the possibility of obtaining a spatially-detailed distribution of the surficial features.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a small part of the area showing distinctive differences in the radar-derived spring transition date is selected for further investigation of microwave scattering properties. The permafrost characteristics in the Yakutsk area have been relatively well studied as compared to other high-latitude regions [23][24][25][26][27]. This region is covered with forests, grasslands and thermokarst features underlain by continuous permafrost.…”
Section: Study Area and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In this region, the August SWE usually has a greater influence on the tree-ring parameters than the June or July SWE (Tei, Sugimoto, Yonenobu, Hoshino, et al, 2013;Tei, Sugimoto, Yonenobu, Yamazaki, et al, 2013). In June, more water is usually available for plants because of infiltration of snowmelt water (Sugimoto et al, 2002Lopez et al, 2015), which then gradually decreases from July to August. Table 2).…”
Section: Multi-year Effects Of Environmental Conditions On Larch Trmentioning
confidence: 99%